Discussion on the Implementation of the Teacher's Marketplace Program on the Career Follow-up of PPG Private Students - ., Bahri; Azmi Mustari, Ulul; Dewi Riang Tati, Andi (KnE Social Sciences, 2024)
Marketplace is a database of prospective teachers that schools can recruit directly from. Parties that can be included in the Teacher Marketplace database are honorary teachers who have passed the P1 selection and are graduates of Pre-service PPG, so that the teacher recruitment process becomes simpler according to the needs of teacher formation in each school. However, this policy discourse received positive and negative responses from various groups, including PPG Pre-service Batch I and II 2022 students in terms of continuing their careers. This study intends to learn more about the teacher marketplace system that is anticipated to be implemented in 2024, the opinions of PPG Prabatan students on the debate over introducing the teacher marketplace, and what the best response to this debate should be using a descriptive approach and a qualitative research method, with the data source being relevant references and interviews. The study’s findings demonstrate that the teacher marketplace system, one of which is intended for pre-service PPG alumni students, is viewed as being more adaptable and simpler to use in deploying teachers in accordance with school demands. PPG Pre-service students, however, objected to the appellation “Teacher Marketplace” being used for this policy. Therefore, the government is expected to consider this policy properly. Keywords: education, teacher, teacher marketplace